Reconfiguring Higher Education: Faculty Development and Interdisciplinary Digital Innovation in the AI Era (International Journal of Computer Science and Engineering, 2026)
The accelerating confluence of artificial intelligence and higher education necessitates a profound structural reconfiguration of traditional academic paradigms. However, bridging the systemic gap between individualized faculty development and broader interdisciplinary digital innovation presents unforeseen empirical complexities; during our framework formulation, initial linear assumptions required substantial iterative adjustments to account for deeply entrenched departmental silos. Drawing upon an evolutionary matrix, this paper delineates the shifting dynamics of AI literacy training, tracing its transition from mechanical tool acquisition to collaborative human-AI pedagogical ecosystems. While data indicators suggest that personalized micro-credentialing potentially catalyzes instructional agility, multi-perspective interpretations indicate that institutional inertia and latent algorithmic biases might, to some extent, obfuscate these positive outcomes. Considering the above factors, this evolutionary trajectory appears inherently non-linear, thereby necessitating further research into decentralized governance and adaptive policy frameworks. Ultimately, this inquiry transcends immediate procedural summaries, elevating the discourse to a theoretical height where the co-evolution of faculty upskilling and interdisciplinary convergence is positioned as an indispensable prerequisite for cultivating future resilient educational ecosystems.